2017
DOI: 10.1177/0271678x17702668
|View full text |Cite
|
Sign up to set email alerts
|

ZO-1 expression is suppressed by GM-CSF via miR-96/ERG in brain microvascular endothelial cells

Abstract: The level of granulocyte-macrophage colony-stimulating factor (GM-CSF) increases in some disorders such as vascular dementia, Alzheimer's disease, and multiple sclerosis. We previously reported that in Alzheimer's disease patients, a high level of GM-CSF in the brain parenchyma downregulated expression of ZO-1, a blood-brain barrier tight junction protein, and facilitated the infiltration of peripheral monocytes across the blood-brain barrier. However, the molecular mechanism underlying regulation of ZO-1 expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 59 publications
0
22
0
Order By: Relevance
“…TJs regulate permeability of the blood-brain barrier (BBB) [ 31 ]. In light of findings that GM-CSF modulates TJ components claudin-5 [ 32 ] and zonula occludens-1 (ZO-1) [ 33 ] thereby altering transendothelial migration of mouse monocytes, we asked if human GM-CSF would also induce similar effects in human brain endothelial cells. rhGM-CSF was added to cultured BEC for 2, 6, 24 and 48 h. A significant decrease in claudin-5 levels in GM-CSF treated BEC was observed 24 and 48 h post stimulation ( Figure 1 c).…”
Section: Resultsmentioning
confidence: 99%
“…TJs regulate permeability of the blood-brain barrier (BBB) [ 31 ]. In light of findings that GM-CSF modulates TJ components claudin-5 [ 32 ] and zonula occludens-1 (ZO-1) [ 33 ] thereby altering transendothelial migration of mouse monocytes, we asked if human GM-CSF would also induce similar effects in human brain endothelial cells. rhGM-CSF was added to cultured BEC for 2, 6, 24 and 48 h. A significant decrease in claudin-5 levels in GM-CSF treated BEC was observed 24 and 48 h post stimulation ( Figure 1 c).…”
Section: Resultsmentioning
confidence: 99%
“…Shang et al have indicated that GM-CSF down-regulates the expression of ZO-1 and claudin-5 in HBMECs, which induces the disruption of tight junctions in BBB (46). Additionally, in another study, intracerebroventricular injection of GM-CSF to wild-type mice was accompanied by a decrease in ZO-1expression in comparison to the PBS group (47) (Figure 1).…”
Section: The Impact Of Gm-csf On Blood-brain Barrier (Bbb) Permeabilitymentioning
confidence: 87%
“…The inhibition of miR-96 has also been shown to be critical in the context of the pathogenesis of Alzheimer’s disease, according to a study performed in brain microvascular endothelial cells in response to granulocyte-macrophage colony-stimulating factor 48 . Furthermore, miR-96 -mediated downregulation of RAD51 in cancer cell lines increases their sensitivity to chemotherapy agents and leads to cell death 35 , a result similar to our observations in pulmonary microvascular endothelial cells upon inhibition of bone morphogenetic protein signaling.…”
Section: Discussionmentioning
confidence: 99%